A formação de professores de matemática no timor-leste à luz da etnomatemática - Belo, Joaquim do Carmo (2010)
This dissertation aims to investigate/realise, in generally, the reflections about the education practiced in the three distinct periods – The Portuguese colonization (1522-1975), The Indonesian invasion (1975-1999) and The East Timor Independent (2002- current) – and, particulary, about Mathematics teachers´ formation in East Timor, by the lights of Ethnomathematics perspective. The point of view here is taken part in “choosing” this theme which makes the sum aspects importance’s to give the contributions through the reflection and to give opportunities for new perspectives as a way of difference views about the multiple issues to improve the quality of scholar education for the country. In particular, the Mathematics teachers training in the country of sandalwood that survived for at least two periods of domination and which “legacy” left by the oppressors of efforts, still needs efforts to be surpassed. For that, it was proposed as theoretical framework of the research, the field of Ethnomathematics –which one is mainly based on the author D’Ambrosio – and allied to the approach of Paulo Freire’s perspective education lode to substance reflections related to significant sources, documents and experiences lived by the researcher. Methodologically, the study includes a component of critical, theoretical and empirical reflection, requiring the author's subjective involvement in the collection of the primary and secondary data. The research was conducted through bibliographic and documentary procedures with ethnographic inspiration and involved a self-critical dialogue of the researcher taking into account his own experience in school practice. Referring to the conceptions of principals authors which as theoretical ground fundaments of this research; discuss as appointment, to the formation of teachers (mathematics) of East Timor, the education of peace, to the citizen and to the world civilization. Emerges for there a new position regarding to the “choices” about knowledge and curriculum for the class room’s practice, which comes to contribute towards the enhancement of the existing knows/makes in East Timor’s socio-cultural context.